Sustentación de caso: propuesta documental autobiográfico respecto a la pandemia COVID - 19, “Puentes flotantes” - Huaman Huillca, Melissa Steffany (2020)
Floating Bridges is an autobiographical short film that explores how to survive the uncertain situation caused by the COVID-19 pandemic. Through a filmed diary, family videos and digital media, the experiences of the past, present and future are questioned. What do we need to do to cope with an uncertain and chaotic reality? The protagonist, through introspection, recognizes, understands and manifests herself. Mental healthcare is the first step in starting a new journey.